Asosiasi antara marka SSR dengan ketahanan terhadap wereng batang coklat pada varietas dan calon galur harapan padi - Chaerani Chaerani; Dwinita W. Utami; Nurul Hidayatun; Buang Abdullah; Bambang Suprihatno (Perhimpunan Entomologi Indonesia, 2014)
Development of resistant rice varieties to brown planthopper (BPH, Nilaparvata lugens Stål) must be countinuously conducted to overcome the spatial and temporal genetic change in BPH into more virulent ones which can adapt to resistance rice. The availability of linked molecular markers with BPH resistant trait can speed up selection of hybridization progenies. Close-linked markers with trait of interest can be identified using association studies between markers and phenotypic data of unrelated individuals without the need to generate hybridization progenies as an alternative method to linkage studies which use mapping population. The objective of this study was to analyze the association of rice simple sequence repeat (SSR) markers with resistance to BPH. Forty-four rice varieties and promising lines with known resistance degree to BPH biotype 3 were assessed using 30 rice microsatellite markers previously mapped in the rice chromosomal regions with effects on resistance to BPH. Association test between SSR markers and BPH resistance scores revealed eight markers (RM17, RM38, RM125, RM144, RM250, RM287, RM328, dan RM536) which were significantly associated with BPH resistance (R2=0,18 to 0,89; P<0,05). Twenty-one varieties and 11 promising lines were detected to contain SSR alleles that were associated with BPH resistance. Marker RM17 was detected in 15 varieties and 11 promising lines which were scored as resistant and moderately resistant to BPH and therefore it is potentially the most useful as early diagnostic marker to detect BPH resistance alleles. Nevertheless, to obtain SSRs that can be used as reliable selection markers for BPH resistance, marker analysis in segregating populations for the eight markers is still needed as well as association test of more SSR markers widely distributed in rice chromosomes.